Lively Interpretation Menguak Hermeniutika Khaleed Abou el-Fadhl - Moh Zunaidi Halimi (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
The hermeneutics conceived by Abou El-Fadhl should be one of the methods of interpretation of Islamic texts. because the process is simple, holistic and requires his hermeneutics with some conditions of significance. somewhat similar to the requirements of Mufassir in the Qur'anic commentary though not as a whole. but in the context of the interpretation of the Qur'an by using the methodology of Hermeneutics which was initiated by Abou El-Fadhl, the author is not covered in its use but chose to withdraw methodological aspects of the interpretation of the Qur'an related to the commentators that did not exist in the Qur'an contemporary hermeneutics, to be more sharp and not falling into the error of determining the meaning of the text desired by the author.